Legal Consequences Of Unilaterally Canceling A Music Concert Ticket Contract - Hussein Alaydrus; Mutia Cherawaty Thalib; Nurul Fazri Elfikri (Yayasan Cerdas Pedia Indonesia, 2026)
Unilateral cancellations of music concerts by promoters significantly harm consumers, particularly with the rise of digital ticket sales. This article examines the legal implications of such cancellations and the liability of promoters for consumer losses. It utilizes normative legal research methods focusing on legislation and concepts. Findings indicate that unilateral cancellations may constitute a default on ticket sales contracts and could breach consumer protection rules if transparent information and proper compensation are not provided. A promoter’s liability may only be dismissed under force majeure if it can be proportionately proven. Consumers can seek remedies including ticket price refunds and compensation for tangible and intangible losses. The enforcement of consumer rights through non-litigation and litigation avenues is also discussed, alongside a recommendation for stricter consumer protection standards in concert organization to avert future issues.